Sustained gut dysbiosis and intestinal inflammation show correlation with weight gain in person with chronic HIV infection on antiretroviral therapy - Ishizaka, Aya; Koga, Michiko; Mizutani, Taketoshi; Suzuki, Yutaka; Matano, Tetsuro; Yotsuyanagi, Hiroshi (BMC microbiology, 2024)
Person with human immunodeficiency virus type-1 (PWH) are prone to chronic inflammation due to residual viral production, even with antiretroviral therapy (ART), which increases the risk of age-related diseases. There is also limited information on changes in the intestinal environment of PWH during ART. In this longitudinal study, we investigated changes in the gut microbiota, persistence of chronic inflammation, interactions between the gut environment and inflammation, and metabolic changes in PWH using long-term ART. We analyzed changes in clinical parameters and gut microbiota in 46 PWH over a mean period of 4 years to understand the influence of gut dysbiosis on inflammation. Overall, changes in the gut microbiota included a decrease in some bacteria, mainly involved in short-chain fatty acid (SCFA) production, and an increase in certain opportunistic bacteria. Throughout the study period, an increase in bacterial-specific metabolic activity was observed in the intestinal environment. Continued decline in certain bacteria belonging to the Clostridia class and metabolic changes in gut bacteria involved in glucose metabolism. Additionally, patients with a low abundance of Parabacteroides exhibited low bacterial alpha diversity and a significant increase in body mass index (BMI) during the study period. Monocyte chemoattractant protein 1, a marker of macrophage activation in the plasma, continued to increase from baseline (first stool collection timepoint) to follow-up (second stool collection timepoint), demonstrating a mild correlation with BMI. Elevated BMI was mild to moderately correlated with elevated levels of plasma interleukin 16 and chemokine ligand 13, both of which may play a role in intestinal inflammation and bacterial translocation within the gut microbiota. The rate of BMI increase correlated with the rate of decrease in certain SCFA-producing bacteria, such as Anaerostipes and Coprococcus 3. Our data suggest that despite effective ART, PWH with chronic inflammation exhibit persistent dysbiosis associated with gut inflammation, resulting in a transition to an intestinal environment with metabolic consequences. Moreover, the loss of certain bacteria such as Parabacteroides in PWH correlates with weight gain and may contribute to the development of metabolic diseases.